MOTIVASI KLIEN DENGAN KEPATUHAN MINUM OBAT PADA PENDERITA HIPERTENSI - Mella Mahardika; Adyani, Sang Ayu Made (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Hypertension is a non-communicable disease and is one of the highest causes of mobirdity and mortality in the world. Conditions like this require treatment for a long time and even a lifetime, so the successful treatment of this disease requires compliance in treatment. The purpose of this study was to determine the relationship between client motivation and compliance with hypertension in taking medication. The design of this study is descriptives with a cross sectional approach and data analysis using the chi-square test. The number of samples used was 144 respondents through a purposive sampling technique. The research instruments used the TMQ (Treatment Motivation Questionnaire) questionnaire, and MMAS-8 (Morisky Medication Adherence Scale). The results of the study found that there was arelationship between client motivation and adherence to taking medication with p-value = 0.000 (p <0.005). This shows that there is a relationship between client motivation and medication adherence in hypertension sufferers Self-motivation is needed for clients so that hypertension therapy can be achieved according to the target.